A case report of primary central nervous system lymphoma with intestinal obstruction as the initial symptom. Issue 10 (March 2018) - Li, Xiaoke; Qi, Shuo; Jiao, Yuntao; Gao, Jing; Du, Hongbo
Abstract: Rationale: Primary central nervous system lymphoma (PCNSL) with initial manifestations of constipation and intestinal obstruction (IO) is rare. Patient concerns: A 50-year-old Chinese male patient was admitted to the gastroenterology department due to constipation and abdominal distention for 8 days. He had experienced intermittent back pain for 3 years prior to admission. Based on abdominal radiography, he was initially diagnosed with IO and treated with meal restriction and enemas. However, his symptoms worsened, and progressive lower limb weakness was observed. Diagnoses: A colonoscopy was inconclusive due to the IO. Computed tomography and magnetic resonance imaging revealed space-occupying lesions near centrums 9–11 of the thoracic vertebrae. The patient underwent spinal decompression surgery, and pathologic examination led to a diagnosis of PCNSL (diffuse large B cell lymphoma). Outcomes: The symptoms of the IO improved postoperatively, and the patient partially recovered his lower limb muscle strength. He returned to his homeland for chemotherapy. Lessons: IO can be an initial, unspecific symptom of spinal cord compression in patients with PCNSL.